The linguistic features of texting and their utilization in a WhatsApp group of English major students - Rusfandi, R; Kurniawati, Desi; Liskinasih, Ayu (Universitas Muhammadiyah Purwokerto, 2025)
This research investigates the linguistic features present in text messaging among students enrolled in an English literature program. The study specifically examines the WhatsApp group